2017
DOI: 10.1155/2017/5934254
|View full text |Cite
|
Sign up to set email alerts
|

Fuzheng Quxie Decoction Ameliorates Learning and Memory Impairment in SAMP8 Mice by Decreasing Tau Hyperphosphorylation

Abstract: Hyperphosphorylation of the microtubule-associated protein, tau, is critical to the progression of Alzheimer's disease (AD). Fuzheng Quxie Decoction (FQD), a Chinese herbal complex, is an effective clinical formula used to treat AD. In the current study, we employed high-performance liquid chromatography and liquid chromatography tandem mass spectrometry to identify the components of FQD. Three major components (ginsenoside Rg1, ginsenoside Re, and coptisine) were detected in the brain of FQD-fed mice, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…In the central nervous system, cognitive impairment and decline in old age are primarily driven by the accumulation of age-related neuropathologies, and old age is thus the primary risk factor for neurodegenerative diseases such as AD (Boyle et al, 2017). Previous studies have shown that YQF extract significantly ameliorates cognitive impairment and protects cerebrovascular function in SAMP8 and APP/PS1 mice (Yang et al, 2017;Wang et al, 2018;Yang et al, 2019). Moreover, the main active ingredients of YQF extract were detected by liquid chromatography tandem mass spectrometry (LC-MS/MS), and alkaloids like berberine, palmatine, worenine, and protopine, and ginsenosides like Rg1, Re, Rb1, Rd, and Rc were found in plasma, while berberine, palmatine, epiberberine, coptisine, and ginsenoside Rb1 were found in brain tissue (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system, cognitive impairment and decline in old age are primarily driven by the accumulation of age-related neuropathologies, and old age is thus the primary risk factor for neurodegenerative diseases such as AD (Boyle et al, 2017). Previous studies have shown that YQF extract significantly ameliorates cognitive impairment and protects cerebrovascular function in SAMP8 and APP/PS1 mice (Yang et al, 2017;Wang et al, 2018;Yang et al, 2019). Moreover, the main active ingredients of YQF extract were detected by liquid chromatography tandem mass spectrometry (LC-MS/MS), and alkaloids like berberine, palmatine, worenine, and protopine, and ginsenosides like Rg1, Re, Rb1, Rd, and Rc were found in plasma, while berberine, palmatine, epiberberine, coptisine, and ginsenoside Rb1 were found in brain tissue (Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There was 3.71 g of crude drug per gram of the extract. Components were detected by HPLC as described by Yang et al 24 Memantine was obtained from the National Institute for Food and Drug Control (batch number H20120268; Beijing, China), produced by Lundbeck (Copenhagen, Denmark). When used, the extract and memantine were dissolved separately in distilled water at intended concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study indicated that FQD was able to reduce tau hyperphosphorylation, 24 but the underlying mechanistic basis was not determined. Therefore, in this study, active components of FQD were screened and possible targets and regulatory pathways predicted by network pharmacology.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations